User awareness and effectiveness of IT security. - Fu, YongZhang. (2011)
Information Technology transformed the way people executed their tasks at work. With the information security policy and security technology in place, it was assumed that an organization would be secured and less vulnerable to security attacks. However, humans were more often than not the weakest link in the security defense line. Many organizations often overlooked the importance of monitoring employee’s behavior and setting their attitude and mindset right in dealing with security events.